2011
DOI: 10.1016/j.neuro.2010.12.013
|View full text |Cite
|
Sign up to set email alerts
|

Lead exposure during synaptogenesis alters NMDA receptor targeting via NMDA receptor inhibition

Abstract: N-methyl-D-aspartate receptor (NMDAR) ontogeny and subunit expression are altered during developmental lead (Pb 2+ ) exposure. However, it is unknown whether these changes occur at the synaptic or cellular level. Synaptic and extra-synaptic NMDARs have distinct cellular roles, thus, the effects of Pb 2+ on NMDAR synaptic targeting may affect neuronal function. In this communication, we show that Pb 2+ exposure during synaptogenesis in hippocampal neurons altered synaptic NMDAR composition, resulting in a decre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
77
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(85 citation statements)
references
References 43 publications
7
77
1
Order By: Relevance
“…On the protein level, a recent study showed that Pb exposure resulted in the decrease in NR2A-containing NMDARs at synaptogenesis in a cell culture system [25]. Thus, it is not surprising that the NR2A expression both in protein and mRNA level were decreased significantly in adult hippocampus during juvenile Pb exposure.…”
Section: Postsynaptic Nr2a and Phosphorylated Glur1 Expressions Synamentioning
confidence: 99%
“…On the protein level, a recent study showed that Pb exposure resulted in the decrease in NR2A-containing NMDARs at synaptogenesis in a cell culture system [25]. Thus, it is not surprising that the NR2A expression both in protein and mRNA level were decreased significantly in adult hippocampus during juvenile Pb exposure.…”
Section: Postsynaptic Nr2a and Phosphorylated Glur1 Expressions Synamentioning
confidence: 99%
“…Exposure to Pb 2+ appears to inhibit both excitatory postsynaptic currents (EPSCs) and inhibitory postsynaptic currents (IPSCs), resulting in reduced neurotransmission in the glutamatergic and GABAergic systems associated with hippocampal neurons [131] . Moreover, expression levels of presynaptic proteins synaptophysin (Syn) and synaptobrevin (Syb) were both reduced, accompanied by reduction in the release of vesicular neurotransmitters associated with glutamatergic and GABAergic synapses, in the presence of Pb 2+ [132] . Further studies have reported that adverse effects of Pb 2+ on the GABAergic system during CNS development is dependent on the level of exposure, and the stage of development [21] , where low concentrations of Pb 2+ (50 ppb) reduced expression of GABA genes at 48 hours post-fertilization (hpf), but subsequently increased gene expression at 60 hpf, at the same concentration.…”
Section: ɣ-Aminobutyric Acid (Gaba)b Receptorsmentioning
confidence: 99%
“…Moreover, the hippocampus appears to be particularly vulnerable as in this brain structure NMDA receptors undergo subunit specific changes during developmental Pb2+ exposure . Exposure to Pb2+ during synaptogenesis causes decreased expression of hippocampal NR2A-subunit of NMDARs at synapses and increased targeting of NR2B-NMDARs to dendritic spines (without increased NR2B-NMDARs expression) (Nihei and Guilarte, 1999;Neal et al, 2011;Zhang et al, 2002).…”
Section: Empirical Support For Linkagementioning
confidence: 99%